The runaway kidney: a rare case of a parastomal hernia with partial kidney herniation. Issue 5 (1st June 2020) - Livezey, Jonathan B; Bolock, Alexa M; Farrell, Timothy J
Abstract: Although parastomal hernias are a common complication of ostomy formation, herniation of intra-abdominal organs, aside from intestine, is infrequent. Furthermore, herniation of retroperitoneal organs, such as the kidney, is an extremely rare finding. We report the case of a 59-year-old male with a right ileostomy who presented with an acute kidney injury with suggestive urinary tract infection. A computed tomography scan revealed a left proximal ureteral stone with left hydronephrosis and a prominent right parastomal hernia with herniation of the mesenteric/retroperitoneal fat, portion of the right kidney, right proximal ureter and some bowel. The patient was taken to the operating room for a left cystourethroscopy with stent placement and made a full recovery. Due to the patient's extensive surgical history, high risk of postoperative infection and lack of evidence demonstrating functional impairment of the right kidney, surgical intervention was not recommended at the present time.